ALPHA WOMEN IN GENDER RELATIONS - Candra Candra; Samsul Ariyadi (Indonesian Journal of Islamic Studies (IJIS), 2026)
This article presents a critical analysis of the phenomenon of Alpha Women in the context of gender relations, particularly in urban professional environments. This research aims to explore the roles, challenges, and theoretical and practical contributions of women with alpha personality tendencies in modern organizations. Using qualitative and quantitative methodological approaches, this study collected data through in-depth interviews and descriptive surveys during the period January 2021 to December 2022. Thematic analysis and descriptive statistics reveal the dynamics of power structures and their impact on gender relations in the workplace. The results of the study show that the role of Alpha Women not only brings leadership innovation but also creates tension in established gender relations. The resulting theoretical implications contribute to the development of gender theory and managerial practice, thus opening up new spaces for dialogue on gender equality in the professional environment.